Studi PerbandinganKemampuan Membaca Al-Qur'an Anak-Anak Desa Pidoli Lombang Kab. Madina dengan Menggunakan Metode Iqra dan Metode Al-Barqy - Nurhayani Nurhayani (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2023)
This research is about a comparative study of children's ability to read the Koran in Pidoli Lombang Madina village using the lqra' method and al-Barqy method, to find out how much children's ability to read the Koran uses the iqra method. al-barqy and wanted to know how the comparison speed of children's Al-Quran reading abilities using the igra method with the al-barqy method in Pidoli Lombang Village, Madina Regency. The data collected was classified into qualitative and quantitative data. Meanwhile, to prove the hypothesis of this research, statistical analysis is used here, namely the